The phenotypic impact of the male-specific region of chromosome-Y in inbred mating: the role of genetic variants and gene duplications in multiple inbred rat strains. Issue 1 (December 2016) - Prokop, Jeremy; Tsaih, Shirng-Wern; Faber, Allison; Boehme, Shannon; Underwood, Adam; Troyer, Samuel; Playl, Lauren; Milsted, Amy; Turner, Monte; Ely, Daniel; Martins, Almir; Tutaj, Marek; et al.
Abstract Backgound The male-specific region of chromosome-Y (MSY) contributes to phenotypes outside of testis development and has a high rate of evolution between mammalian species. With a lack of genomic crossover, MSY is one of the few genomic areas under similar variation and evolutionary selection in inbred and outbred animal populations, allowing for an assessment of evolutionary mechanisms to translate between the populations. Methods Using next-generation sequencing, MSY consomic strains, molecular characterization, and large-scale phenotyping, we present here regions of MSY that contribute to inbred strain phenotypes. Results We have shown that (1) MSY of rat has nine autosomal gene transposition events with strain-specific selection; (2) sequence variants in MSY occur with a 1.98-fold higher number of variants than other chromosomes in seven sequenced rat strains; (3)Sry, the most studied MSY gene, has undergone extensive gene duplications, driving ubiquitous expression not seen in human or mouse; (4) the expression profile ofSry in the rat is driven by the insertion of theSry2 copy into an intron of the ubiquitously expressed Kdm5d gene in antisense orientation, but due to several loss of function mutations in theSry2 protein, nuclear localization and transcriptional control are decreased; (5) expression ofSry copies other thanSry2 in the rat overlaps with the expression profile for humanSRY ; (6) gene duplications and sequence variants (P76T) ofSry can be selected for phenotypes such as high blood pressure and androgen receptor signaling within inbred mating; and most importantly, (7) per chromosome size, MSY contributes to higher strain-specific phenotypic variation relative to all other chromosomes, with 53 phenotypes showing both a male to female and consomic cross significance. Conclusion The data presented supports a high probability of MSY genetic variation altering a broad range of inbred rat phenotypes.